ELEKTRON TA’LIM TUSHUNCHASINING USLUBIY ASOSLARI - Khasanov Abdushohid Abdurashidovich (Educational Research in Universal Sciences, 2024)
This article reveals the methodological foundations of the concept of e-learning and presents the qualities and analysis of its development.